Dendritic Cell-Targeted Approaches to Modulate Immune Dysfunction in the Tumor Microenvironment - Gallois, Anne; Bhardwaj, Nina (Frontiers in Immunology, 2013)
There has been enormous progress this past decade in the understanding of the biology of dendritic cells (DCs) along with increasing attention for the development of novel DC-based cancer therapies. However, the clinical impact of DC-based vaccines remains to be established. This limited success could be explained by suboptimal conditions for generating potent immunostimulatory DCs as well as immune suppression mediated by the tumor microenvironment. Therefore, strategies that optimize the potency of DC vaccines along with newly described therapies that target the tumor microenvironment in order to overcome immune dysfunction may provide durable tumor-specific immunity. These novel interventions hold the most promise for successful cancer immunotherapies.